Vasoactive intestinal polypeptide and cholinergic mechanisms in cat nasal mucosa: studies on choline acetyltransferase and release of vasoactive intestinal polypeptide. - Lundberg, J M (1981)
Quantitative immunohistochemical analysis of the sphenopalatine ganglion in normal cats revealed that virtually all ganglion cells (98.5%) were immunoreactive to vasoactive intestinal polypeptide (VIP). After surgical removal of this ganglion, the content of both VIP and choline acetyltransferase (acetyl-CoA:choline O-acetyltransferase, EC 2.3.1.6), a specific marker for cholinergic neurons, was decreased to about 70-80% in the nasal mucosa. In contrast, in animals subjected to sympathectomy combined with sensory (trigeminal) denervation, no significant change in VIP or choline acetyltransferase was found in the nasal mucosa. The present findings strongly suggest that a large proportion of the VIP neurons in the sphenopalatine ganglion contain choline acetyltransferase. This further supports the view that VIP is present in a population of autonomic cholinergic neurons innervating exocrine glands in the cat. In contrast, the ciliary ganglion contained high levels of choline acetyltransferase but no VIP. Parasympathetic nerve stimulation (15 Hz) caused a maximal vasodilation and a 500-fold increase in VIP output from the nasal mucosa. The plasma VIP immunoreactivity eluted at the same position as porcine VIP on gel permeation chromatography. Atropine pretreatment, which is known to abolish nasal secretion, caused a further 3-fold increase in VIP output during the nerve stimulation (15 Hz). Simultaneously, a markedly prolonged duration of the vasodilatory response was observed. The increased output of VIP during parasympathetic nerve stimulation by atropine pretreatment suggests that the transmitter acetylcholine may inhibit the release of the coexisting peptide--i.e., VIP--via muscarinic autoreceptors.